Peran Operator Sekolah dalam Peningkatan Pelayanan Publik di Era Digital di SD Negeri 6 Watampone Kabupaten Bone - Muh. Fadli Mangenre; Erwin; Syamsuddin (Southeast Asian Journal of Islamic Education Management, 2024)
This research discusses the role of school operators in enhancing the effectiveness of public services in the digital era at SD Negeri 6 Watampone, Bone Regency. The research method used is qualitative. This study aims to understand the role of school operators in improving public services at SD Negeri 6 Watampone. The approach taken is a descriptive qualitative approach, with data collection techniques including interviews and observations. The results of the study show that the role of school operators in the effectiveness of public services in the digital era at SD Negeri 6 Watampone, Bone Regency, can be observed through their performance in carrying out their duties as school operators. School operators handle educational administrative activities at SD Negeri 6 Watampone, starting from student administration, curriculum administration, teacher and staff administration, to facility and infrastructure administration. In terms of management, school operators meet the requirements through recruitment, followed by training and development processes. The development of the school operator’s performance focuses on their main duties in the area of educational administration at SD Negeri 6 Watampone. Additionally, school operators are granted data access rights related to SD Negeri 6 Watampone. Furthermore, the services provided by the school operators have been adequately fulfilled, as evidenced by their performance. Despite facing unexpected and undesired obstacles, the school operators were able to overcome these challenges and deliver good results.